Proceedings of 35th International Cosmic Ray Conference — PoS(ICRC2017) 2017
DOI: 10.22323/1.301.0856
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric monitoring and array calibration in CTA using the Cherenkov Transparency Coefficient

Abstract: The Cherenkov Telescope Array (CTA) will be the next generation observatory employing different types of Cherenkov telescopes for the detection of particle showers initiated by very-highenergy gamma rays. A good knowledge of the Earth's atmosphere, which acts as a calorimeter in the detection technique, will be crucial for calibration in CTA. Variations of the atmosphere's transparency to Cherenkov light and not correctly performed calibration of individual telescopes in the array result in large systematic un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In previous publications, a phenomenological approach was used to link the measured trigger rate with properties of the atmosphere [e.g. 6,7]. The goal of the presented study is to find a physics driven fit model to describe the measured trigger rates for hadron induced showers (background) and gamma induced events (signal) as a function of the observed zenith angle θ.…”
Section: Introductionmentioning
confidence: 99%
“…In previous publications, a phenomenological approach was used to link the measured trigger rate with properties of the atmosphere [e.g. 6,7]. The goal of the presented study is to find a physics driven fit model to describe the measured trigger rates for hadron induced showers (background) and gamma induced events (signal) as a function of the observed zenith angle θ.…”
Section: Introductionmentioning
confidence: 99%
“…Lidars, FRAM and AERONET Sun/Moon photometer). The preliminary results of a feasibility study for the application of the CTC in CTA are reported in a separate contribution in these proceedings [21].…”
Section: Further Devices and Methods In Developmentmentioning
confidence: 99%
“…Additionally to that, redundant information is obtained for calibration and cross-checks by photometric measurements of reference stars using a sophisticated, portable small-aperture multi-pixels photon detector, the UVScope and the UVSiPM [58,59] and the "Cherenkov Transparency Coefficient" (CTC) calculated directly from science data [60].…”
Section: Aerosol Characterization Of the Observed Field-of-view By Ctamentioning
confidence: 99%